Electroencephalogram and Alzheimer's Disease: Clinical and Research Approaches. (24th April 2014) - Tsolaki, Anthoula; Kazis, Dimitrios; Kompatsiaris, Ioannis; Kosmidou, Vasiliki; Tsolaki, Magda
Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder that is characterized by cognitive deficits, problems in activities of daily living, and behavioral disturbances. Electroencephalogram (EEG) has been demonstrated as a reliable tool in dementia research and diagnosis. The application of EEG in AD has a wide range of interest. EEG contributes to the differential diagnosis and the prognosis of the disease progression. Additionally such recordings can add important information related to the drug effectiveness. This review is prepared to form a knowledge platform for the project entitled "Cognitive Signal Processing Lab, " which is in progress in Information Technology Institute in Thessaloniki. The team tried to focus on the main research fields of AD via EEG and recent published studies.